1991
DOI: 10.3354/cr001117
|View full text |Cite
|
Sign up to set email alerts
|

Estimating daily global radiation from air temperature and rainfall measurements

Abstract: Radiation-mediated processes (e.g. photosynthesis, evapotranspiration) can be simulated on the basis of measured incoming radiation. Since irradiance is measured at very few weather stations it is often estimated from the duration of bright sunshine or from mean daily cloudiness. In the absence of both these variables, irradiance can be estimated by means of satellite images, spatial interpolation techniques or standard meteorological observations. In this paper, a model to estimate daily global radiation from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
17

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 19 publications
0
18
0
17
Order By: Relevance
“…Examples of this approach are the works of Brinsfield et al (1984), Bristow and Campbell (1984), Hargreaves et al (1985), Donatelli and Marletto (1994), Donatelli and Campbell (1998). Other methods also use rainfall measurements (Hodges et al, 1985;Reddy, 1987;McCaskill, 1990;Bindi and Miglietta, 1991;Hook and McClendon, 1992;Nikolov and Zeller, 1992;Elizondo et al, 1994). Hunt et al (1998) compared several of the above methods.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of this approach are the works of Brinsfield et al (1984), Bristow and Campbell (1984), Hargreaves et al (1985), Donatelli and Marletto (1994), Donatelli and Campbell (1998). Other methods also use rainfall measurements (Hodges et al, 1985;Reddy, 1987;McCaskill, 1990;Bindi and Miglietta, 1991;Hook and McClendon, 1992;Nikolov and Zeller, 1992;Elizondo et al, 1994). Hunt et al (1998) compared several of the above methods.…”
Section: Introductionmentioning
confidence: 99%
“…There is more heating during daytime due to large proportions of direct solar radiation, whereas at night time temperatures drop further down since the outgoing long-wave radiation is not reflected by clouds. Numerous studies investigating the relationship between DTR and radiation (Pan et al, 2013;Makowski et al, 2009;Bindi and Miglietta, 1991;Bristow and Campbell, 1984) show considerable correlations. For example, Makowski et al (2009) reported a correlation coefficient of 0.87 of the annual means of DTR and solar radiation averaged over 31 stations across Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature-related models were also derived by several researchers such as Allen (1997), Liu et al (2009), Meza andVaras (2000), and Thornton and Running (1999). Both temperatureand precipitation-based models were developed by Bindi and Miglietta (1991), Liu and Scott (2001), Thornton et al (2000), and Winslow et al (2001). Unfortunately, there are very few or limited studies on solar radiation estimation models for Bangladesh (Podder et al 2014;Khan et al 2014;Khadem et al 2007;Rahman et al 1999;Ghosh et al 2006).…”
Section: Introductionmentioning
confidence: 99%